2005
DOI: 10.1007/s10453-005-9001-z
|View full text |Cite
|
Sign up to set email alerts
|

Transport efficiency and deposition velocity of fluidized spores in ventilation ducts

Abstract: Experiments with dry, fluidized spores were conducted in a test apparatus to delineate the extent of spore contamination and deposition behavior under normal airflow conditions within a ventilation system. The surrogate biological warfare agent used in experiments was the spore-forming bacterium Bacillus atrophaeus. Viable-spore-counting methods were used in the study because they provide the most important number for estimating human health effects. Three common ventilation duct materials were evaluated: flex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…These airspeeds correspond to the typical low velocity airflow within buildings that has been studied by other investigators (e.g., Górny et al, 2002;Kildesø et al, 2003). The effects of the much higher airspeeds that are measured in ventilation ducts (Krauter et al, 2005) were not studied. Spores released from the samples were captured on Micro5 Microcell cassettes (EMS) or Cyclex-D impactor cassettes (EMS) that were connected between the cuvette outflow and pump inlet.…”
Section: Microflow Apparatus For Studying Spore Dispersalmentioning
confidence: 92%
“…These airspeeds correspond to the typical low velocity airflow within buildings that has been studied by other investigators (e.g., Górny et al, 2002;Kildesø et al, 2003). The effects of the much higher airspeeds that are measured in ventilation ducts (Krauter et al, 2005) were not studied. Spores released from the samples were captured on Micro5 Microcell cassettes (EMS) or Cyclex-D impactor cassettes (EMS) that were connected between the cuvette outflow and pump inlet.…”
Section: Microflow Apparatus For Studying Spore Dispersalmentioning
confidence: 92%
“…The deposition of spores on the surface was not measured in all experiments but was conducted the same as in previous experiments (12). For those experiments where direct mea- surement of the surface deposition was not available, deposition was estimated by using the ratio S meas /C meas from data collected in prior experiments and using the following equation:…”
Section: Shortmentioning
confidence: 99%
“…In previous deposition experiments surrogate BWA were used in three common ventilation duct materials: flexible plastic, galvanized steel, and internally insulated fiberglass. Spore transport efficiency ranged from 9 to 13% in steel and fiberglass ducts; transport efficiency was far less (0.1 to 4%) in plastic duct (12). Results showed that the deposition of surrogate BWA was significantly different in the three duct materials evaluated.…”
mentioning
confidence: 91%
See 2 more Smart Citations